Impact of Maternal Parenting Approaches in Dental Care on Behavioral Modification and Oral Hygiene of Primary School Children in Banda Aceh - Rahayu, Eka Sri; Reca, Reca; Salfiyadi, Teuku; Jauhari, Julianti; Andriany, Poppy; Putri, Citra Feriana (Journal of Health Science and Medical Therapy, 2025)
Children’s oral health is significantly influenced by parental involvement, particularly maternal parenting practices in daily care routines. This study aimed to analyze the effect of maternal parenting within the context of dental nursing care on behavioral changes and oral hygiene status among primary school children in Banda Aceh. A quasi-experimental design with a pre-test and post-test control group was employed. The sample consisted of 60 children aged 7–8 years and their mothers, divided into an intervention group (n = 30), which received structured education and supervised parenting guidance, and a control group (n = 30), which only received educational modules. Data were collected at three stages: pre-test, post-test I (immediately after the intervention), and post-test II (two weeks later). Findings revealed a significant improvement in mothers’ knowledge, attitudes, and practices regarding dental health in the intervention group compared to the control group (p < 0.05). Furthermore, the oral hygiene status of children, measured by the Patient Hygiene Performance-Modified (PHP-M) index, showed a statistically significant reduction in scores in the intervention group, indicating better oral cleanliness, while no significant changes were observed in the control group (p > 0.05). These results demonstrate that parenting-based dental health education effectively enhances maternal involvement in guiding and supervising children’s oral care, thereby fostering improved oral health behaviors and hygiene outcomes. The study concludes that maternal parenting approaches within dental nursing care have a substantial impact on improving both maternal dental health practices and children’s oral hygiene status.